Securitization, bank lending and credit quality: the case of Spain - Santiago Carbó-Valverde; David Marqués-Ibá\~nez; Francisco Rodríguez Fernández (European Central Bank (ECB), 2011)
While the 2007-2010 financial crisis has hit a variety of countries asymmetrically, the case of Spain is particularly illustrative: this country experienced a pronounced housing bubble partly funded via spectacular developments in its securitization markets leading to looser credit standards and subsequent financial stability problems. We analyze the sequential deterioration of credit in this country considering rating changes in individual securitized deals and on balance sheet bank conditions. Using a sample of 20,286 observations on securities and rating changes from 2000Q1 to 2010Q1 we build a model in which loan growth, on balancesheet credit quality and rating changes are estimated simultaneously. Our results suggest that loan growth significantly affects on balance-sheet loan performance with a lag of at least two years. Additionally, loan performance is found to lead rating changes with a lag of four quarters. Importantly, bank characteristics (in particular, observed solvency, cash flow generation and cost efficiency) also affect ratings considerably. Additionally, these other bank characteristics seem to have a higher weight in the rating changes of securities issued by savings banks as compared to those issued by commercial banks.
Keywords: G21; G12; 330; financial instability; lending; risk; securitization